Respuesta :

Step-by-step explanation
Ver imagen chinmayeeBTS

Step-by-step explanation:

[tex] \tt{2 {x}^{2} + 5x - 3 = 0}[/tex]

⇢ [tex] \sf{2 {x}^{2} + 5x + ( - 3) = 0}[/tex]

Here , a = 2 , b = 5 & c = -3 {a is the coefficient of x² , b is the coefficient of x and c is the constant term }

Now ,

[tex] \tt{x = \frac{ - b± \sqrt{ {b}^{2} - 4ac } }{2a} }[/tex]

⇢ [tex] \tt{x = \frac{ - 5± \sqrt{ {5}^{2} - 4 \times 2 \times ( - 3) } }{2 \times 2} }[/tex]

⇢ [tex] \sf{ x= \frac{ - 5±7}{4} }[/tex]

Taking positive ( + ) sign :

⇝[tex] \tt{x = \frac{ - 5 + 7}{4} = \frac{1}{2}} [/tex]

Taking negative ( - ) sign :

⇝[tex] \tt{x = \frac{ - 5 - 7}{4} = - 3}[/tex]

[tex] \purple{ \boxed{ \boxed{ \tt{⤑ \: Our \: final \: answer : \boxed{ \underline{ \tt{x = \frac{1}{2} , \: - 3}}}}}}}[/tex]

Hope I helped ! ツ

Have a wonderful day / night♡

▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁